Turnpike phenomenon for averaged optimal control - Hernández Salinas, Martin; Lazar, Martin; Zamorano, Sebastián (Optimization, 2026)
Our main contribution in this article is to prove the turnpike property in both its integral and exponential forms for parameter-dependent systems with averaged optimal control. Specifically, under suitable assumptions about the matrices defining the system dynamics and the cost functional, we prove that the optimal control and state for the time-dependent problem converge, on average, to the optimal pair of the associated stationary problem. Furthermore, we quantify the proximity between these two optimal solutions, proving that, over a sufficiently long time interval, they remain exponentially close.
CRIS-Team Scopus Importer:2026-02-27
Keywords: averaged optimal control; Parameter dependent problem; turnpike property